2018
DOI: 10.4049/jimmunol.1800343
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Interaction Sites on Human Chemokine Receptors by Deep Mutational Scanning

Abstract: Chemokine receptors CXCR4 and CCR5 regulate WBC trafficking and are engaged by the HIV-1 envelope glycoprotein gp120 during infection. We combine a selection of human CXCR4 and CCR5 libraries comprising nearly all of ∼7000 single amino acid substitutions with deep sequencing to define sequence-activity landscapes for surface expression and ligand interactions. After consideration of sequence constraints for surface expression, known interaction sites with HIV-1-blocking Abs were appropriately identified as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 83 publications
5
104
0
Order By: Relevance
“…These included the interactions between CXCR4 E26 and CXCL12 R47, along with CXCR4 D20 and CXCL12 K56 ( Fig 5, S1 Data). Previous one-sided mutagenesis studies have suggested a role for D20 and E26 in CXCL12 binding [53,54]; however, their functional role has not been verified. Moreover, their exact pairing with CXCL12 residues in the complex has never been explored.…”
Section: Validation Of Prospective Predictions From the Model In A Fumentioning
confidence: 89%
“…These included the interactions between CXCR4 E26 and CXCL12 R47, along with CXCR4 D20 and CXCL12 K56 ( Fig 5, S1 Data). Previous one-sided mutagenesis studies have suggested a role for D20 and E26 in CXCL12 binding [53,54]; however, their functional role has not been verified. Moreover, their exact pairing with CXCL12 residues in the complex has never been explored.…”
Section: Validation Of Prospective Predictions From the Model In A Fumentioning
confidence: 89%
“…The Ctermini of myc-tagged MHC-I were fused to VN (a.a. V1-A154 of Venus I152L mutant) (71). Cloning of tagged CXCR4 fusions to VN and VC are previously described (72). All constructs were cloned into pCEP4 (Invitrogen), and targeted mutations were generated by site directed mutagenesis and confirmed with DNA sequencing.…”
Section: Supporting Information Supporting Methodsmentioning
confidence: 99%
“…The media was replaced 2 hours post transfection. Under these conditions, cells typically acquire no more than a single coding sequence (72).…”
Section: Bimolecular Fluorescence Complementation Expi293f Cells Atmentioning
confidence: 99%
“…9,31 There are more than 20 chemokine receptors in the human body, 40 of which only 2 have a complete mutational dataset. 41 Evaluating TLmutation algorithms on these two datasets will allow us to uncover essential insights into other chemokine receptors and HIV pathology.…”
Section: Case Study 1: Completing Gaps In Experimental Datasetsmentioning
confidence: 99%
“…In this case study, we utilized available single point mutation datasets for two proteins, CXCR4 and CCR5, and two different experiments, expression level and bimolecular fluorescence complementation (BiFC) assay. 41 Sequence identity and similarity between CXCR4 and CCR5 are ∼ 30% and 50%, respectively ( Figure 5). The proposed supervised and unsupervised TLmutation algorithms were implemented and shown for one case of supervised transfer and four different cases of unsupervised transfer.…”
Section: Case Study 1: Completing Gaps In Experimental Datasetsmentioning
confidence: 99%